The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/mnfr.201400480
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent effects of isoflavone exposure during early lifetime on the rat mammary gland: Studies on estrogen sensitivity, isoflavone metabolism, and DNA methylation

Abstract: Lifelong exposure to ISO results in dose-dependent differential effects on proliferation, gene expression, and DNA methylation in rat mammary glands. Yet, a decrease in estrogen responsiveness was only achieved by IRDhigh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 57 publications
(71 reference statements)
2
24
2
Order By: Relevance
“…PhyEs exposure during adolescence modulated the adult mammary gland sensitivity to E 2 and lifelong exposure resulted in dose-dependent differential effects on proliferation, gene expression, and DNA methylation in rat mammary glands. Further studies will be necessary to clarify their effective role, considering that response varies from different race and ethnicity (Blei et al, 2015). The preventive role of PhyEs if assumed during adolescence was also supported by the result of a study showing that intake of PhyEs during adolescence among Ontario women was associated with a reduced risk of developing breast cancer (Anderson et al, 2013).…”
Section: Natural Xenoestrogensmentioning
confidence: 99%
“…PhyEs exposure during adolescence modulated the adult mammary gland sensitivity to E 2 and lifelong exposure resulted in dose-dependent differential effects on proliferation, gene expression, and DNA methylation in rat mammary glands. Further studies will be necessary to clarify their effective role, considering that response varies from different race and ethnicity (Blei et al, 2015). The preventive role of PhyEs if assumed during adolescence was also supported by the result of a study showing that intake of PhyEs during adolescence among Ontario women was associated with a reduced risk of developing breast cancer (Anderson et al, 2013).…”
Section: Natural Xenoestrogensmentioning
confidence: 99%
“…Isoflavones appear to modulate epigenetic mechanisms, including DNA methylation, histone modifying genes and noncoding RNAs [38]. Some of the genes suffering DNA methylation, after exposure to high or low doses of isoflavones [39], regulate the proliferation of mammary epithelial cells. Our study has effectively demonstrated the differential expression of a proliferation marker in castrated rats induced by isoflavones.…”
Section: Discussionmentioning
confidence: 99%
“…A clear dose response pattern cannot always be observed [39]. According Blei et al, an isoflavone dose that reflects a lifelong nutritional exposure via a soy rich diet may be sufficient to result in an increase in fat metabolism, protein synthesis and skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Details and permission for the soy intervention study in rats are described in ref. [42]. Details and ethical approval for the human broccoli intervention study are described in ref.…”
Section: Compliance With Ethics Guidelinesmentioning
confidence: 99%
“…One of the aims in this project is to investigate the influence soy isoflavones on estrogen sensitivity of mammary glands [42]. Isoflavones are phyto-estrogenic plant compounds and could therefore attenuate physiological changes associated with hormone deprivation [43].…”
Section: Mcip-seq After Dietary Soy Intervention In Healthy Wistar Ratsmentioning
confidence: 99%